Ultrasonographic Evaluation of Gastric Content During Labor Under Epidural Analgesia: A Prospective Cohort Study. Issue 1 (March 2015) - Bataille, A.; Rousset, J.; Marret, E.; Bonnet, F.
Abstract : ( Br J Anaesth . 2014;112(4):703–707)